Political secularism, religion, and the state a time series analysis of worldwide data - Fox, Jonathan 1968- (Cambridge studies in social theory, religion and politics., 2015)
This book examines 111 types of state religion policy in 177 countries between 1990 and 2008. Jonathan Fox argues that policy is largely a result of the competition between political secular actors and religious actors, both of which try to influence state religion policy. While there are other factors that influence state religion policy and both the secular and religious camps are divided, Fox offers that the secular-religious competition perspective provides critical insight into the nature of religious politics across the globe. While many states have both increased and decreased their involvement in religion, Fox demonstrates that states which have become more involved in religion are far more common.